Digital Population Identity (IKD): Implementation Of Public Policy Innovations And Efforts To Realize Single Identity Number (SIN) - Kevin Brizi; Martani Huseini (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Transformation in the public service sector is taking place so quickly and significantly, this is in line with advances in various sectors, especially the information technology sector. Public services in Indonesia today lead to a New Public Services (NPS) paradigm where the focus of the services provided is on fulfilling public interests and satisfaction. In achieving and or realizing this paradigm, it is very necessary to have an integral and comprehensive policy innovation, where a policy innovation must focus on creating high value or value and come from a collaboration carried out by all parties to improve the quality of performance of the organization. Policy innovations related to public services that will be discussed in this study, aim to describe the efforts made by the Government through a Digital Population Identity (IKD) policy innovation which will lead to the realization of a Single Identity Number (SIN) in the future to provide convenience in services. The research method to be carried out is a qualitative approach, namely literature review techniques and literature reviews derived from academic literacy and other supporting references, and strengthened by interview techniques for the fulfillment of data and other supporting information.